Polymer catalyst, preparation method and application thereof, and method for preparing polyether
By directly connecting catalytic active groups on the polymer main chain, the self-support and high catalytic activity of the organic catalyst are achieved, and the problems of large loading of existing catalysts and low catalytic efficiency are solved, and the development of green chemical industry in polyether production is achieved.
Patent Information
- Application Number
- CN202311368419.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
The existing organic catalysts have problems such as large loading, low catalytic efficiency, and difficulty in separation and recycling in polyether production, which limits the development of green chemical industry of the polyether industry.
By directly connecting the catalytically active groups to the backbone of the polymer, the catalyst is self-supported, and the solubility of the catalyst is regulated through structural design, so that homogeneous catalysis is achieved while being easy to recover and separate.
It achieves high catalytic activity and self-loading characteristics, reduces energy consumption, simplifies the separation and recovery process of catalysts, and is suitable for industrial production of polyethers.
Smart Images

Figure CN119859261A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic catalysts, and in particular relates to a polymer catalyst and a preparation method thereof and an application method and a method for preparing polyether. Background Art
[0002] Polyether is a common synthetic material. Due to its rich and diverse structures, it can be used as lubricants, surfactants and defoamers in the metal industry, building materials, clothing industry, medicine and batteries. At present, the industrial production of polyether mainly uses metal catalysts, such as potassium hydroxide (KOH), double metal cyanide (DMC) and Van den Berg catalyst. Although these metal catalysts are widely used, their low catalytic efficiency, high energy consumption and heavy metal pollution have limited the development of the polyether industry towards green chemical industry.
[0003] In the past few decades, organic catalysts have attracted the attention of the scientific and industrial communities and made great progress due to their advantages such as cheap availability, non-toxicity, environmental friendliness, easy handling and storage, opening up new prospects for the preparation of fine chemicals and polymer materials. The development of organic catalysts and their application in synthesis are expected to break the long-term limitations in the field of polyethers and inject new vitality into polyether production. In order to facilitate the separation and recovery of catalysts, organic catalysts are generally loaded on insoluble carriers for use, but this will lead to the occurrence of heterogeneous reactions and reduce the catalytic reaction rate. In addition, for some reactions with large catalyst loading, agglomeration and aggregation are also easily formed, which increases the difficulty of recovery and recycling.
[0004] In order to achieve the goals of high catalytic efficiency and easy recovery and separation at the same time, researchers have developed polymer-supported organic catalysts. The catalytically active groups are connected to the side chains of inert polymers (such as polyethylene) to make them soluble in the reaction system, catalyze the homogeneous reaction, increase the catalytic reaction rate, and are easy to remove (precipitate by adding solvent) at the end of the reaction and may be recycled. However, one disadvantage of this strategy is that the inert polymer carrier reduces the loading level of the catalyst, increases the amount of solvent required for the reaction, and consumes a lot of energy, which is not suitable for the industrial production of polyethers. In summary, it is currently urgent to develop organic catalysts with low loading, high catalytic efficiency, easy separation and recovery, and recyclable for use in the polyether industry.
[0005] To solve this problem, the catalytically active groups are directly connected to the main chain instead of the side chain of the inert polymer, thereby achieving self-loading of the catalyst and solving the problem of low loading of the supported catalyst. Through reasonable structural design, the solubility of the self-supported polymer catalyst is regulated, so that it can achieve homogeneous catalysis and be easy to recover and separate. Summary of the invention
[0006] The technical problem to be solved by the present invention is the defects of large organic catalyst loading, low catalytic efficiency, and difficulty in separation and recovery in the prior art. A self-supporting polymer catalyst and its preparation method and application in polyether synthesis are proposed. The self-supporting polymer catalyst is a copolymer of benzotriazole and borane-substituted benzene ring. This method of directly connecting two catalytically active groups alternately to the main chain realizes the self-loading of the polymer catalyst and solves the energy consumption problem caused by the large loading of the organic catalyst. The rigid structure of the two catalytically active groups reduces the solubility of the catalyst, which is conducive to the separation and recovery of the catalyst.
[0007] To achieve the purpose of the present invention, in a first aspect, the present invention provides a polymer catalyst having a structure of formula α:
[0008]
[0009] Wherein, R1 is an alkyl group, an alkoxy group or an aromatic group;
[0010] R2 and R3 are the same or different and are each independently a H atom, an alkyl group, an alkoxy group or an aromatic group;
[0011] Y and Z are the same or different and are each independently an alkyl group, an alkoxy group, a nitro group or an ester group;
[0012] X is a halogen atom;
[0013] n is a natural number ranging from 5 to 50.
[0014] As a specific embodiment of the present invention, R1 is a C1-C6 alkyl group, a C1-C6 alkoxy group or a C6-C10 aromatic group, preferably an ethyl group or a methoxy group;
[0015] and / or, R2 is an H atom, a C1-C6 alkyl group, a C1-C6 alkoxy group or a C6-C10 aromatic group, preferably an H atom or an ethyl group or a methoxy group;
[0016] and / or, R3 is an H atom, a C1-C6 alkyl group, a C1-C6 alkoxy group or a C6-C10 aromatic group, preferably an H atom or a methoxy group;
[0017] and / or, Y is C1-C8 alkyl, C1-C8 alkoxy, nitro or ethoxy, preferably methyl or nitro;
[0018] and / or, Z is C1-C8 alkyl, C1-C8 alkoxy, nitro or ethoxy, preferably methyl or nitro;
[0019] And / or, X is a fluorine atom, a chlorine atom or a bromine atom, preferably a chlorine atom.
[0020] And / or, n is a natural number ranging from 5 to 20.
[0021] In a second aspect, the present invention provides a method for preparing the polymer catalyst, as shown in Formula 1, the method comprises the following steps:
[0022] S1: Compound 1 undergoes an alkylation reaction with compound 2 to obtain compound 3;
[0023] S2: Compound 3 undergoes bromination reaction to obtain compound 4;
[0024] S3: Compound 4 is polymerized to obtain the polymer catalyst.
[0025]
[0026] As a specific embodiment of the present invention, the step S1 comprises: adding a strong base reagent such as NaH or an organic lithium reagent to compound 1 to replace active hydrogen, and then adding compound 2 to carry out an alkylation reaction; the compound 2 is a benzene ring substituted with organic boron.
[0027] As a specific embodiment of the present invention, in the step S1, the temperature for replacing active hydrogen is in the range of -20°C to 20°C, for example, -20°C, -10°C, -50°C, 0°C, 5°C, 10°C, 20°C and any combination thereof; the time is 0.5h to 3h; for example, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h and any combination thereof.
[0028] As a specific embodiment of the present invention, in the step S1, the temperature of the alkylation reaction is 20°C to 60°C, for example, in the range of 20°C, 30°C, 40°C, 50°C, 60°C and any combination thereof.
[0029] The time is 1 hour to 6 hours, for example, the range of 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours and any combination thereof.
[0030] As a specific embodiment of the present invention, in step S1, the reaction solvent is selected from toluene, xylene, tetrahydrofuran, diethyl ether, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide, preferably dimethyl sulfoxide.
[0031] As a specific embodiment of the present invention, the step S2 comprises: adding a bromination reagent to compound 3 to carry out a bromination reaction, wherein the bromination reagent is preferably tribromoisocyanuric acid (TBCA);
[0032] As a specific embodiment of the present invention, in step S2, the temperature of the bromination reaction is 20°C to 100°C; for example, in the range of 20°C, 40°C, 60°C, 80°C, 100°C and any combination thereof.
[0033] As a specific embodiment of the present invention, in step S2, the time of the bromination reaction is 0.5h to 24h; for example, the range of 0.5h, 3h, 6h, 12h, 24h and any combination thereof.
[0034] As a specific embodiment of the present invention, in step S2, the reaction solvent is one of dichloromethane, chloroform, dichloroethane, toluene, xylene, chlorobenzene, and dichlorobenzene, preferably toluene and chloroform;
[0035] As a specific embodiment of the present invention, in step S2, the concentration of compound 3 is 0.05-0.2 mol / L.
[0036] As a specific embodiment of the present invention, in the step S3, the temperature of the polymerization reaction is 80°C to 140°C, for example, in the range of 80°C, 100°C, 120°C, 140°C and any combination thereof.
[0037] As a specific embodiment of the present invention, in step S3, the reaction time is 12 hours to 72 hours, for example, in the range of 12 hours, 24 hours, 48 hours, 72 hours and any combination thereof.
[0038] As a specific embodiment of the present invention, in step S3, the reaction solvent is selected from N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), dimethyl sulfoxide (DMSO), dichloroethane, toluene, xylene, chlorobenzene and dichlorobenzene, preferably toluene and chlorobenzene.
[0039] As a specific embodiment of the present invention, in step S3, the concentration of compound 4 is 0.05-0.1 mol / L.
[0040] In a third aspect, the present invention provides a method for preparing polyether by ring-opening polymerization of an epoxy compound, comprising the following steps:
[0041] SⅠ: Add epoxy compound and initiator into the reactor under nitrogen atmosphere;
[0042] SⅡ: dissolving the polymer catalyst according to claim 1 or 2 or the polymer catalyst prepared by the preparation method according to any one of claims 3 to 6 in a solvent, and then adding it to the reactor of step SⅠ;
[0043] SⅢ: The reactor of step SⅡ is heated and stirred for reaction. After the reaction is completed, the polymer catalyst is precipitated and filtered to recover the catalyst. The filtrate is a crude polyether product.
[0044] As a specific embodiment of the present invention, in step SⅠ, the epoxy compound is selected from one or more of propylene oxide, 1,2-butylene oxide, 1,4-butylene oxide, 3-methylbutylene oxide, 1,2-pentene oxide, 2-ethyl-3-methylethylene oxide, 1,2-hexylene oxide, hexylene oxide, 1,2-heptane oxide, and cyclohexane oxide.
[0045] As a specific embodiment of the present invention, in step SⅠ, the initiator is a monohydric alcohol compound, selected from one of methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, pentanol, isopentanol, n-hexanol, 2-hexanol, and 3-hexanol.
[0046] As a specific embodiment of the present invention, in step SⅠ, the mass ratio of the initiator to the epoxy compound is 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and any combination thereof; preferably 4% to 6%.
[0047] As a specific embodiment of the present invention, in step SⅡ, the solvent of the catalyst is a polar aprotic solvent selected from one of acetone, acetonitrile, dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), and hexamethylphosphoramide (HMP); preferably DMF.
[0048] As a specific embodiment of the present invention, in the step SⅡ, the mass ratio of the catalyst to the epoxy compound is 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% and any combination thereof; preferably 0.3% to 0.6%.
[0049] As a specific embodiment of the present invention, in step SⅡ, the concentration of the catalyst solution is 10% to 60% (mass fraction), for example, 10%, 20%, 30%, 40%, 50%, 60%; preferably 20% to 40%.
[0050] As a specific embodiment of the present invention, in the step SIII, the reaction temperature is 30°C to 80°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C; preferably 40°C to 60°C.
[0051] As a specific embodiment of the present invention, the stirring rate is 200 to 1000 rpm; preferably 500 to 800 rpm.
[0052] As a specific embodiment of the present invention, in the step SIII, the reaction time is 3h to 12h, for example, 3h, 6h, 9h, 12h and any combination thereof.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] 1. The polymer catalyst of the present invention is synthesized by copolymerization of benzotriazole and borane-substituted benzene rings. Two catalytically active groups are alternately connected to the main chain, and the self-loading and high catalytic activity of the polymer catalyst are achieved, solving the energy consumption problem caused by the large loading of the organic catalyst. The rigid structure of the two catalytically active groups reduces the solubility of the catalyst, which is conducive to the separation and recovery of the catalyst.
[0055] 2. Compared with the prior art, the present invention has the following advantages: the main chain of the polymer catalyst provided by the present invention is a catalytically active group connected alternately, has the characteristics of self-support and high catalytic activity and monomer conversion rate, and can be used as a homogeneous catalyst for the synthesis of polyethers. On this basis, the catalyst also has the advantages of easy recovery and reusability. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 is the structural formula of the polymer catalyst in Examples 1-6 of the present invention. DETAILED DESCRIPTION
[0057] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0058] The molecular structure of the polymer catalyst of the present invention can be as follows Figure 1 The structure shown.
[0059] Embodiment 1-6 is Figure 1 Synthesis of polymer catalysts I-VI shown.
[0060] Example 1
[0061] This embodiment provides a polymer catalyst and a preparation method thereof, the specific details are as follows:
[0062]
[0063] (1) Under anhydrous and oxygen-free conditions, 5.00 g of compound 1 (34.0 mmol, 1.0 eq) was dissolved in 100 mL of dimethyl sulfoxide, 1.48 g of 60% NaH solution (37 mmol, 1.1 eq) was added at 0°C, reacted for 1 h, and then 13.1 g of compound 2 (37 mmol, 1.1 eq) was added. The temperature was raised to 60°C and stirred for 6 h. After the reaction was completed, the solvent was distilled off under reduced pressure, and the solid in the bottle was washed with ethanol several times and dried to obtain 13.0 g of compound 3, with a yield of 92%.
[0064] (2) 10.0 g of compound 3 (24.0 mmol, 1.0 eq) and 2.89 g of TBCA (7.9 mmol, 0.33 eq) were dissolved in 200 mL of chloroform and heated to 40° C. for 6 h. After the reaction, the solvent was distilled off and recrystallized to obtain 10.9 g of compound 4 with a yield of 92%.
[0065] (3) 5.00 g of compound 4 (10.1 mmol, 1.0 eq) was dissolved in 100 mL of chlorobenzene and heated to 120° C. for 24 h. After the reaction, the reaction solution was cooled to room temperature, ethanol was added to precipitate solids, and 4.1 g of catalyst I was obtained by filtration, with a number average molecular weight of 5215 g / mol and a yield of 98%.
[0066] Example 2
[0067] This embodiment provides a polymer catalyst and a preparation method thereof, the specific details of which are as follows:
[0068]
[0069] (1) Under anhydrous and oxygen-free conditions, 5.00 g (34.0 mmol, 1.0 eq) of compound 1 was dissolved in 100 mL of dimethyl sulfoxide, 1.48 g of 60% NaH solution (37 mmol, 1.1 eq) was added at -10°C, reacted for 0.5 h, 14.6 g of compound 2 (37 mmol, 1.1 eq) was added, the temperature was raised to 40°C, and the reaction was stirred for 9 h. After the reaction was completed, the solvent was distilled off under reduced pressure, the solid in the bottle was washed with ethanol several times, and dried to obtain 14.0 g of compound 3, with a yield of 90%.
[0070] (2) 10.0 g of compound 3 (21.9 mmol, 1.0 eq) and 2.64 g of TBCA (7.2 mmol, 0.33 eq) were dissolved in 200 mL of toluene and heated to 80° C. for 3 h. After the reaction, the solvent was distilled off and recrystallized to obtain 11.3 g of compound 4 with a yield of 96%.
[0071] (3) 5.00 g of compound 4 (9.3 mmol, 1.0 eq) was dissolved in 100 mL of chlorobenzene and heated to 140° C. for 24 h. After the reaction, the reaction solution was cooled to room temperature, ethanol was added to precipitate solids, and 4.0 g of catalyst II was obtained by filtration, with a number average molecular weight of 5920 g / mol and a yield of 95%.
[0072] Example 3
[0073] This embodiment provides a polymer catalyst and a preparation method thereof, the specific details of which are as follows:
[0074]
[0075] (1) Under anhydrous and oxygen-free conditions, 5.00 g (34.0 mmol, 1.0 eq) of compound 1 was dissolved in 100 mL of dimethyl sulfoxide, 1.48 g of 60% NaH solution (37 mmol, 1.1 eq) was added at 10°C, and after reacting for 1 h, 15.8 g of compound 2 (37 mmol, 1.1 eq) was added, the temperature was raised to 80°C, and the reaction was stirred for 3 h. After the reaction was completed, the solvent was distilled off under reduced pressure, the solid in the bottle was washed with ethanol several times, and after drying, 14.6 g of compound 3 was obtained, with a yield of 88%.
[0076] (2) 10.0 g of compound 3 (20.4 mmol, 1.0 eq) and 2.47 g of TBCA (6.8 mmol, 0.33 eq) were dissolved in 200 mL of chloroform and heated to 40° C. for 3 h. After the reaction, the solvent was distilled off and recrystallized to obtain 10.6 g of compound 4 with a yield of 91%.
[0077] (3) 5.00 g of compound 4 (8.8 mmol, 1.0 eq) was dissolved in 100 mL of toluene, and the temperature was raised to 100° C. for reaction for 48 h. After the reaction was completed, the reaction solution was cooled to room temperature, ethanol was added to precipitate solids, and 4.1 g of catalyst III was obtained by filtration, with a number average molecular weight of 7830 g / mol and a yield of 96%.
[0078] Example 4
[0079] This embodiment provides a polymer catalyst and a preparation method thereof, the specific details of which are as follows:
[0080]
[0081] (1) Under anhydrous and oxygen-free conditions, 5.00 g (20.7 mmol, 1.0 eq) of compound 1 was dissolved in 100 mL of dimethyl sulfoxide, 0.9 g of 60% NaH solution (22.8 mmol, 1.1 eq) was added at 0°C, and after reacting for 2 h, 8.92 g of compound 2 (22.8 mmol, 1.1 eq) was added, the temperature was raised to 30°C, and the reaction was stirred for 12 h. After the reaction was completed, the solvent was distilled off under reduced pressure, the solid in the bottle was washed with ethanol several times, and after drying, 10.6 g of compound 3 was obtained, with a yield of 93%.
[0082] (2) 10.0 g of compound 3 (18.2 mmol, 1.0 eq) and 2.20 g of TBCA (6.0 mmol, 0.33 eq) were dissolved in 200 mL of chloroform and heated to 40° C. for 12 h. After the reaction, the solvent was distilled off and recrystallized to obtain 10.7 g of compound 4 with a yield of 93%.
[0083] (3) 5.00 g of compound 4 (8.4 mmol, 1.0 eq) was dissolved in 100 mL of chlorobenzene, and the temperature was raised to 100° C. for reaction for 72 h. After the reaction was completed, the reaction solution was cooled to room temperature, ethanol was added to precipitate solids, and 4.1 g of catalyst IV was obtained by filtration, with a number average molecular weight of 6742 g / mol and a yield of 94%.
[0084] Example 5
[0085] This embodiment provides a polymer catalyst and a preparation method thereof, the specific details are as follows:
[0086]
[0087] (1) Under anhydrous and oxygen-free conditions, 5.00 g (20.7 mmol, 1.0 eq) of compound 1 was dissolved in 100 mL of dimethyl sulfoxide, and 0.9 g of 60% NaH solution (22.8 mmol, 1.1 eq) was added at -10°C. After reacting for 1 h, 8.01 g of compound 2 (22.8 mmol, 1.1 eq) was added, the temperature was raised to 40°C, and the reaction was stirred for 6 h. After the reaction was completed, the solvent was distilled off under reduced pressure, and the solid in the bottle was washed with ethanol several times and dried to obtain 10 g of compound 3, with a yield of 94%.
[0088] (2) 10.0 g of compound 3 (19.6 mmol, 1.0 eq) and 2.36 g of TBCA (6.5 mmol, 0.33 eq) were dissolved in 200 mL of toluene and heated to 60° C. for 24 h. After the reaction, the solvent was distilled off and recrystallized to obtain 10.4 g of compound 4 with a yield of 90%.
[0089] (3) 5.00 g of compound 4 (9.0 mmol, 1.0 eq) was dissolved in 100 mL of toluene and heated to 140° C. for 12 h. After the reaction, the reaction solution was cooled to room temperature, ethanol was added to precipitate solids, and 4.2 g of catalyst V was obtained by filtration, with a number average molecular weight of 6110 g / mol and a yield of 91%.
[0090] Example 6
[0091] This embodiment provides a polymer catalyst and a preparation method thereof, the specific details are as follows:
[0092]
[0093] (1) Under anhydrous and oxygen-free conditions, 5.00 g (20.7 mmol, 1.0 eq) of compound 1 was dissolved in 100 mL of dimethyl sulfoxide, 0.9 g of 60% NaH solution (22.8 mmol, 1.1 eq) was added at 10°C, and after reacting for 1 h, 9.38 g of compound 2 (22.8 mmol, 1.1 eq) was added, the temperature was raised to 60°C, and the reaction was stirred for 3 h. After the reaction was completed, the solvent was distilled off under reduced pressure, the solid in the bottle was washed with ethanol several times, and after drying, 10.7 g of compound 3 was obtained, with a yield of 90%.
[0094] (2) 10.0 g of compound 3 (17.5 mmol, 1.0 eq) and 2.11 g of TBCA (5.8 mmol, 0.33 eq) were dissolved in 200 mL of toluene and heated to 80° C. for 12 h. After the reaction, the solvent was distilled off and recrystallized to obtain 10.8 g of compound 4 with a yield of 95%.
[0095] (3) 5.00 g of compound 4 (8.1 mmol, 1.0 eq) was dissolved in 100 mL of toluene, and the temperature was raised to 100° C. for reaction for 24 h. After the reaction was completed, the reaction solution was cooled to room temperature, ethanol was added to precipitate solids, and 4.0 g of catalyst VI was obtained by filtration, with a number average molecular weight of 7633 g / mol and a yield of 95%.
[0096] Examples 7-14 are methods for preparing polyethers
[0097] Example 7
[0098] Under a nitrogen atmosphere, 100 g of propylene oxide and 5 g of n-butanol were added to a Schlenk bottle, 0.5 g of catalyst I was dissolved in 2.0 g of DMF and added to the Schlenk bottle, the temperature was raised to 40°C, and the reaction was stirred for 3 h. After the reaction was completed, the catalyst precipitated, and 0.44 g of the catalyst was recovered by filtration to obtain 94 g of a polyether product.
[0099] Example 8
[0100] Under a nitrogen atmosphere, 100 g of butylene oxide and 5 g of n-butanol were added to a Schlenk bottle, 0.6 g of catalyst II was dissolved in 0.9 g of DMF and added to the Schlenk bottle, the temperature was raised to 40°C, and the reaction was stirred for 6 hours. After the reaction was completed, the catalyst precipitated and 0.56 g of catalyst II was recovered by filtration to obtain 93 g of polyether product.
[0101] Example 9
[0102] Under a nitrogen atmosphere, 100 g of butylene oxide and 4 g of n-butanol were added to a Schlenk bottle, 0.6 g of catalyst II was dissolved in 0.9 g of DMF and added to the Schlenk bottle, the temperature was raised to 60°C, and the reaction was stirred for 3 h. After the reaction was completed, the catalyst precipitated, and 0.55 g of catalyst II was recovered by filtration to obtain 90 g of polyether product.
[0103] Example 10
[0104] Under a nitrogen atmosphere, 100 g of butylene oxide and 3 g of n-butanol were added to a Schlenk bottle, 0.6 g of catalyst II was dissolved in 0.9 g of DMF and added to the Schlenk bottle, the temperature was raised to 60°C, and the reaction was stirred for 3 h. After the reaction was completed, the catalyst precipitated and 0.53 g of catalyst II was recovered by filtration to obtain 85 g of polyether product.
[0105] Embodiment 11
[0106] Under a nitrogen atmosphere, 100 g of butylene oxide and 6 g of n-hexanol were added to a Schlenk bottle, 0.3 g of catalyst III was dissolved in 0.7 g of DMF and added to the Schlenk bottle, the temperature was raised to 60°C, and the reaction was stirred for 12 h. After the reaction was completed, the catalyst precipitated and 0.27 g of catalyst III was recovered by filtration to obtain 89 g of polyether product.
[0107] Example 12
[0108] Under a nitrogen atmosphere, 40 g of butylene oxide, 60 g of cyclohexene oxide and 4 g of n-hexanol were added to a Schlenk bottle, 0.3 g of catalyst IV was dissolved in 0.7 g of DMF and added to the Schlenk bottle, the temperature was raised to 50°C, and the reaction was stirred for 6 hours. After the reaction was completed, the catalyst precipitated and 0.26 g of catalyst IV was recovered by filtration to obtain 92 g of polyether product.
[0109] Example 13
[0110] Under a nitrogen atmosphere, 50 g of propylene oxide, 50 g of 1,2-epoxyhexane and 6 g of n-hexanol were added to a Schlenk bottle, 0.6 g of catalyst IV was dissolved in 0.9 g of DMF and added to the Schlenk bottle, the temperature was raised to 60°C, and the reaction was stirred for 12 h. After the reaction was completed, the catalyst precipitated and 0.57 g of catalyst IV was recovered by filtration to obtain 95 g of polyether product.
[0111] Embodiment 14
[0112] Under a nitrogen atmosphere, 30 g of butylene oxide, 70 g of 1,2-epoxyhexane and 4 g of n-butanol were added to a Schlenk bottle, 1.0 g of catalyst V was dissolved in 1.5 g of DMF and added to the Schlenk bottle, the temperature was raised to 50°C, and the reaction was stirred for 6 hours. After the reaction was completed, the catalyst precipitated and 0.90 g of catalyst V was recovered by filtration to obtain 92 g of polyether product.
[0113] Embodiment 15
[0114] Under a nitrogen atmosphere, 100 g of butylene oxide and 4 g of n-butanol were added to a Schlenk bottle, 0.6 g of catalyst VI was dissolved in 0.9 g of DMF and added to the Schlenk bottle, the temperature was raised to 50°C, and the reaction was stirred for 3 hours. After the reaction was completed, the catalyst precipitated and 0.55 g of catalyst VI was recovered by filtration to obtain 92 g of polyether product.
[0115] Example 16
[0116] Under a nitrogen atmosphere, 100 g of butylene oxide and 4 g of n-butanol were added to a Schlenk bottle, 0.5 g of catalyst VI was dissolved in 0.9 g of DMF and added to the Schlenk bottle, the temperature was raised to 50°C, and the reaction was stirred for 3 hours. After the reaction was completed, the catalyst precipitated and 0.46 g of catalyst VI was recovered by filtration to obtain 95 g of polyether product.
[0117] Embodiment 17
[0118] Under a nitrogen atmosphere, 100 g of butylene oxide and 4 g of n-butanol were added to a Schlenk bottle, 0.4 g of catalyst VI was dissolved in 0.9 g of DMF and added to the Schlenk bottle, the temperature was raised to 50°C, and the reaction was stirred for 3 h. After the reaction was completed, the catalyst precipitated and 0.37 g of catalyst VI was recovered by filtration to obtain 90 g of a polyether product.
[0119] Embodiment 18
[0120] Example 7 Reuse of recovered catalyst: Under a nitrogen atmosphere, 50 g of propylene oxide and 2.5 g of n-butanol were added to a Schlenk bottle, 0.25 g of recovered catalyst I was dissolved in 1.0 g of DMF and added to the Schlenk bottle, the temperature was raised to 40°C, and the reaction was stirred for 3 h. After the reaction was completed, the catalyst precipitated and 0.23 g of the catalyst was recovered by filtration to obtain 46 g of a polyether product.
[0121] Embodiment 19
[0122] Example 8 Recycling of recovered catalyst: Under a nitrogen atmosphere, 50 g of butylene oxide and 2.5 g of n-butanol were added to a Schlenk bottle, 0.3 g of recovered catalyst II was dissolved in 0.45 g of DMF and added to the Schlenk bottle, the temperature was raised to 40°C, and the reaction was stirred for 6 hours. After the reaction was completed, the catalyst precipitated and 0.26 g of catalyst II was recovered by filtration to obtain 46 g of polyether product.
[0123] Embodiment 20
[0124] Example 11 Recycling of recovered catalyst: Under a nitrogen atmosphere, 20 g of butylene oxide, 30 g of cyclohexene oxide and 2 g of n-hexanol were added to a Schlenk bottle, 0.15 g of catalyst IV was dissolved in 0.35 g of DMF and added to the Schlenk bottle, the temperature was raised to 50°C, and the reaction was stirred for 6 hours. After the reaction was completed, the catalyst precipitated and 0.13 g of catalyst IV was recovered by filtration to obtain 46 g of polyether product.
[0125] Test Case
[0126] The polymerization activity was calculated by the ratio of polymer yield (unit: g) to the amount of catalyst added (unit: g). The epoxy monomer conversion rate was obtained by nuclear magnetic resonance hydrogen spectrum analysis, and the test was carried out on a Bruker AVANCE III 400 spectrometer, with TMS as the internal standard, deuterated ether as the deuterated solvent, and the test temperature was 25°C; the molecular weight and molecular weight distribution (polydispersity coefficient) were measured by a room temperature gel permeation chromatograph PL-GPC50, and the detector selected a differential refractive index detector and a light scattering detector in combination, the test temperature was 35°C, the eluent was tetrahydrofuran, the flow rate was 1.00 ml / min, and narrow distribution polystyrene was used for calibration. The test sample was a tetrahydrofuran solution of the polymer (5 mg / mL), and the test volume was 100 μL.
[0127] Table 1 Product properties of Examples 7-14
[0128]
[0129] It can be seen that the self-supported polymer catalyst of the embodiment of the present invention has the advantages of high catalytic activity and monomer conversion rate, and is easy to recycle and reuse.
[0130] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0131] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A polymer catalyst, characterized in that The polymer catalyst has a structure of formula α: Wherein, R1 is an alkyl group, an alkoxy group or an aromatic group; R2 and R3 are the same or different and are each independently a H atom, an alkyl group, an alkoxy group or an aromatic group; Y and Z are the same or different and are each independently an alkyl group, an alkoxy group, a nitro group or an ester group; X is a halogen atom; n is a natural number ranging from 5 to 50.
2. The polymer catalyst according to claim 1, characterized in that R1 is a C1-C6 alkyl group, a C1-C6 alkoxy group or a C6-C10 aromatic group, preferably an ethyl group or a methoxy group; and / or, R2 is an H atom, a C1-C6 alkyl group, a C1-C6 alkoxy group or a C6-C10 aromatic group, preferably an H atom or an ethyl group or a methoxy group; and / or, R3 is an H atom, a C1-C6 alkyl group, a C1-C6 alkoxy group or a C6-C10 aromatic group, preferably an H atom or a methoxy group; and / or, Y is C1-C8 alkyl, C1-C8 alkoxy, nitro or ethoxy, preferably methyl or nitro; and / or, Z is C1-C8 alkyl, C1-C8 alkoxy, nitro or ethoxy, preferably methyl or nitro; And / or, X is a fluorine atom, a chlorine atom or a bromine atom, preferably a chlorine atom. And / or, n is a natural number ranging from 5 to 20.
3. A method for preparing a polymer catalyst according to claim 1 or 2, characterized in that: As shown in formula 1, the following steps are included: S1: Compound 1 undergoes an alkylation reaction with compound 2 to obtain compound 3; S2: Compound 3 undergoes bromination reaction to obtain compound 4; S3: Compound 4 is polymerized to obtain the polymer catalyst.
4. The preparation method according to claim 3, characterized in that: The step S1 comprises: adding a strong base reagent such as NaH or an organic lithium reagent to compound 1 to replace active hydrogen, and then adding compound 2 to carry out an alkylation reaction; the compound 2 is a benzene ring substituted with organic boron; Preferably, the temperature for replacing active hydrogen is -20°C to 20°C, and the time is 0.5h to 3h; and / or, the alkylation reaction temperature is 20° C. to 60° C., and the reaction time is 1 h to 6 h; and / or, the reaction solvent is one of toluene, xylene, tetrahydrofuran, diethyl ether, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide, preferably dimethyl sulfoxide; And / or, the concentration of compound 1 is 0.2-0.6 mol / L.
5. The preparation method according to claim 3 or 4, characterized in that: The step S2 comprises: adding a bromination reagent to compound 3 to carry out a bromination reaction, wherein the bromination reagent is preferably tribromoisocyanuric acid (TBCA); and / or, the temperature of the bromination reaction is 20° C. to 100° C.; and / or, the bromination reaction time is 0.5h to 24h; and / or, the reaction solvent is one of dichloromethane, chloroform, dichloroethane, toluene, xylene, chlorobenzene and dichlorobenzene, preferably toluene and chloroform; And / or, the concentration of compound 3 is 0.05-0.2 mol / L.
6. The preparation method according to any one of claims 3 to 5, characterized in that: In the step S3, the polymerization reaction temperature is 80°C to 140°C; And / or, the polymerization reaction time is 12h to 72h; and / or, the reaction solvent is one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), dimethyl sulfoxide (DMSO), ethylene dichloride, toluene, xylene, chlorobenzene and dichlorobenzene, preferably toluene and chlorobenzene; And / or, the concentration of compound 4 is 0.05-0.1 mol / L.
7. Use of the polymer catalyst according to claim 1 or 2 or the polymer catalyst prepared by the preparation method according to any one of claims 3 to 6 in the field of preparing polyethers by ring-opening polymerization of epoxy compounds.
8. A method for preparing polyether by ring-opening polymerization of epoxy compounds, characterized in that: The steps include: SⅠ: Add epoxy compound and initiator into the reactor under nitrogen atmosphere; SII: adding a polymer catalyst solution containing the polymer catalyst according to claim 1 or 2 or the polymer catalyst prepared by the preparation method according to any one of claims 3 to 6 to the reactor of step SⅠ; SⅢ: The reactor of step SⅡ is heated and stirred for reaction. After the reaction is completed, the polymer catalyst is precipitated and filtered to recover the catalyst. The filtrate is a crude polyether product.
9. The method for preparing polyether by ring-opening polymerization of epoxy compounds according to claim 8, characterized in that: In the step SⅠ, the epoxy compound is selected from one or more of propylene oxide, 1,2-butylene oxide, 1,4-butylene oxide, 3-methylbutylene oxide, 1,2-pentene oxide, 2-ethyl-3-methylethylene oxide, 1,2-hexylene oxide, hexylene oxide, 1,2-heptane oxide, and cyclohexane oxide; And / or, the initiator is a monohydric alcohol compound selected from one of methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, amyl alcohol, isopentanol, n-hexanol, 2-hexanol, and 3-hexanol; And / or, the mass ratio of the initiator to the epoxy compound is 1% to 10%.
10. The method for preparing polyether by ring-opening polymerization of epoxy compounds according to claim 8 or 9, characterized in that: In the step SII, the solvent of the polymer catalyst solution is a polar aprotic solvent, preferably selected from one of acetone, acetonitrile, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, and hexamethylphosphoramide; And / or, the mass ratio of the polymer catalyst to the epoxy compound is 0.1% to 1%; And / or, the concentration of the polymer catalyst solution is 10 wt% to 60 wt%.
11. The method for preparing polyether by ring-opening polymerization of epoxy compounds according to any one of claims 8 to 10, characterized in that: In the step SⅢ, the reaction temperature is 30°C to 80°C; and / or, the stirring rate is 200 to 1000 rpm; And / or, the reaction time is 3h to 12h.